2004
DOI: 10.1590/s0034-72992004000600018
|View full text |Cite
|
Sign up to set email alerts
|

O papel das citocinas no colesteatoma adquirido da orelha média: revisão da literatura

Abstract: Este estudo visa a analisar de modo crítico a literatura pertinente a respeito do papel das citocinas no colesteatoma adquirido. O colesteatoma da orelha média é caracterizado pela presença de epitélio escamoso estratificado queratinizado neste local, com alto poder invasivo, causando destruição óssea e podendo levar a complicações. As citocinas são glicoproteínas de baixo peso molecular que atuam na intercomunicação celular. São importantes na estimulação e supressão dos eventos da resposta imune, desencadean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…The most frequently found inflammatory cells in the perimatrix are lymphocytes, plasmacytes, and macrophages, as also seen by other authors 4,15 . The inflammatory process present in the cholesteatoma perimatrix seems to play an important role in inducing the production of cytokines 16,17 . These proteins can modify the characteristics of the very cells that produced them and of adjacent cells 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently found inflammatory cells in the perimatrix are lymphocytes, plasmacytes, and macrophages, as also seen by other authors 4,15 . The inflammatory process present in the cholesteatoma perimatrix seems to play an important role in inducing the production of cytokines 16,17 . These proteins can modify the characteristics of the very cells that produced them and of adjacent cells 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus, however, about its localization. Alves and Ribeiro 18 (2004) summarized the differences in opinion. (Table 1) the cholesteatoma epithelium (matrix).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Since then many authors have studied the action of TNF-÷ on bone resorption in cholesteatoma. 18 Yan and Huang 11 (1991) analyzed five experimentally induced cholesteatomas in animals and five surgical fragments. They found that human and experimental cholesteatomas had varying degrees of inflammation, including mononuclear infiltrates (lymphocytes and macrophages) and signs of vascular proliferation.…”
Section: Action Of Tnf-α In Acquired Middle Ear Cholesteatomamentioning
confidence: 99%
“…Citokini koji se oslobođaju tokom upalnog procesa u perimatriksu holesteatoma, smatraju se odgovornim za destrukciju kosti, a ističe se da TNF-α zajedno sa aktivatorom receptora nuklearnog kappa-B liganda (RANKL) i IL-1, IL -6 učestvuje u procesu destrukcije i pregradnje kosti [1][2][3].…”
Section: Uvodunclassified